A VERSATILE MODEL OF CARDIAC TISSUE FROM HIPSC-DERIVED CARDIOMYOCYTES WITHIN PERICARDIAL MATRIX HYDROGELS DOPED WITH HYDRAZIDE FUNCTIONALIZED MWCNTS FOR PHARMACEUTICAL SCREENING AND TISSUE ENGINEERING APPLICATIONS - Roshanbinfar, Kaveh; Oommen, Oommen Podiyan; Hilborn, Jons; Engel, Felix (TISSUE ENGINEERING PART A, 2022)
CRIS-Team WoS Importer:2022-08-12

BIOHYBRID HYDROGEL WITH ENHANCED ELECTROCONDUCTIVITY ADVANCES MATURATION OF HIPSC-DERIVED CARDIOMYOCYTES - Roshanbinfar, Kaveh; Engel, Felix (TISSUE ENGINEERING PART A, 2022)
CRIS-Team WoS Importer:2022-08-12

Biomimetic Organic-Inorganic Nanocomposite Scaffolds to Regenerate Cranial Bone Defects in a Rat Animal Model - Moosavifar, Mirjavad; Parsaei, Houman; Hosseini, Seyedjamal; Mirmontazeri, Seyed Mohammad; Ahadi, Reza; Ahadian, Samad; Engel, Felix; Roshanbinfar, Kaveh (ACS Biomaterials Science and Engineering, 2022)
While bone regenerates itself after an injury, a critical bone defect requires external interventions. Engineering approaches to restore bone provide a temporary scaffold to support the damage and provide beneficial biological cues for bone repair. Biomimetically generated scaffolds replicate the naturally occurring phenomena in bone regeneration. In this study, a gelatin-calcium phosphate nanocomposite was synthesized by an efficient and cost-effective double-diffusion biomimetic approach. Calcium and phosphate ions are impregnated in the gelatin, mimicking the natural bone mineralization process. Glutaraldehyde from 0.5 to 2 w/v% was used for gelatin cross-linking and mechanical properties of the scaffold, and its biological support for rat bone marrow mesenchymal stromal cells was analyzed. Analysis of scanning electron microscopy images of the nanocomposite scaffolds and Fourier transform infrared (FTIR) and X-ray diffraction (XRD) characterizations of these scaffolds confirmed precipitation of calcium phosphates in the gelatin. Moreover, lysozyme degradation assay showed that scaffold degradation reversely correlates with the concentration of the cross-linking agent. Increased glutaraldehyde concentrations enhanced the mechanical properties of the scaffolds, bringing them closer to those of cancellous bone. Rat bone marrow mesenchymal stromal cells maintained their viability on these scaffolds compared to standard cell culture plates. In addition, these cells showed differentiation into bone lineage as evaluated from alkaline phosphatase activity up to 21 days and Alizarin red staining of the cells over 28 days. Eventually, scaffolds were implanted in a cranial defect in a rat animal model with a 5 mm diameter. Bone regeneration was studied over 90 days. Analysis of histological sections of the injury and computer tomography images revealed that nanocomposite scaffolds cross-linked with 1% w/v glutaraldehyde provide the maximum bone regeneration after 90 days. Collectively, our data show that nanocomposite scaffolds developed here provide effective regeneration for extensive bone defects in vivo.
CRIS-Team Scopus Importer:2022-04-15
Keywords: biomimetic scaffold; bone tissue engineering; gelatin-calcium phosphate; nanocomposite graft

Carbon nanotube doped pericardial matrix derived electroconductive biohybrid hydrogel for cardiac tissue engineering - Roshanbinfar, Kaveh; Mohammadi, Zahra; Sheikh-Mahdi Mesgar, Abdorreza; Dehghan, Mohammad Mehdi; Oommen, Oommen P.; Hilborn, Jöns; Engel, Felix (Biomaterials Science, 2019)
Cardiovascular diseases represent a major socio-economic burden. In recent years, considerable effort has been invested in optimizing cell delivery strategies to advance cell transplantation therapies to restore heart function for example after an infarct. A particular issue is that the implantation of cells using a non-electroconductive matrix potentially causes arrhythmia. Here, we demonstrate that our hydrazide-functionalized nanotubes-pericardial matrix-derived electroconductive biohybrid hydrogel provides a suitable environment for maturation of human-induced pluripotent stem cell (hiPSC)-derived cardiomyocytes. hiPSC-derived cardiomyocytes exhibited an improved contraction amplitude (>500%) on conductive hydrogels compared to cells cultured on Matrigel®. This was accompanied by increased cellular alignment, enhanced connexin 43 expression, and improved sarcomere organization suggesting maturation of the hiPSC-derived cardiomyocytes. Sarcomeric length of these cells increased from 1.3 to 1.7 μm. Moreover, 3D cell-laden engineered tissues exhibited enhanced calcium handling as well as positive response to external electrical and pharmaceutical stimulation. Collectively, our data indicate that our biohybrid hydrogels consisting of solubilized nanostructured pericardial matrix and electroconductive positively charged hydrazide-conjugated carbon nanotubes provide a promising material for stem cell-based cardiac tissue engineering.
CRIS-Team Scopus Importer:2019-09-03

CHIR99021 Promotes hiPSC-Derived Cardiomyocyte Proliferation in Engineered 3D Microtissues - Hesselbarth, Ramona; Esser, Tilman; Roshanbinfar, Kaveh; Schrüfer, Stefan; Schubert, Dirk W.; Engel, Felix (Advanced Healthcare Materials, 2021)
Cardiac tissue engineering is a promising strategy to generate human cardiac tissues for modeling cardiac diseases, screening for therapeutic drugs, and repairing the injured heart. Yet, several issues remain to be resolved including the generation of tissues with high cardiomyocyte density. Here, it is shown that the integration of the glycogen synthase kinase-3β inhibitor CHIR99021 in collagen I hydrogels promotes proliferation of human-induced pluripotent stem cell-derived (hiPSC) cardiomyocytes post-fabrication improving contractility of and calcium flow in engineered 3D cardiac microtissues. CHIR99021 has no effect on the gelation kinetics or the mechanical properties of collagen I hydrogels. Analysis of cell density and proliferation based on Ki-67 staining indicates that integration of CHIR99021 together with external CHIR99021 stimulation increases hiPSC-cardiomyocyte number by ≈2-fold within 7 d post-fabrication. Analysis of the contractility of engineered cardiac tissues after another 3 d in the absence of external CHIR99021 shows that CHIR99021-induced hiPSC-cardiomyocyte proliferation results in synchronized calcium flow, rhythmic beating, increased speed of contraction and contraction amplitude, and reduced peak-to-peak time. The CHIR99021-stimulated engineered cardiac microtissues exhibit spontaneous rhythmic contractions for at least 35 d. Collectively, the data demonstrate the potential of induced cardiomyocyte proliferation to enhance engineered cardiac microtissues by increasing cardiomyocyte density.
CRIS-Team Scopus Importer:2021-09-17
Keywords: cardiomyocytes; CHIR99021; heart; hiPSC; proliferation; tissue engineering

Collagen Hydrogel Containing Polyethylenimine-Gold Nanoparticles for Drug Release and Enhanced Beating Properties of Engineered Cardiac Tissues - Roshanbinfar, Kaveh; Kolesnik-Gray, Maria; Angeloni, Miriam; Schrüfer, Stefan; Fiedler, Maren; Schubert, Dirk W.; Ferrazzi, Fulvia; Krstic, Vojislav; Engel, Felix (Advanced Healthcare Materials, 2023)
Cardiac tissue engineering is a promising strategy to prevent heart failure. However, several issues remain unsolved, including efficient electrical coupling and incorporating factors to enhance tissue maturation and vascularization. Herein, a biohybrid hydrogel that enhances beating properties of engineered cardiac tissues and allows drug release concurrently is developed. Gold nanoparticles (AuNPs) with different sizes (18–241 nm) and surface charges (33.9–55.4 mV) are synthesized by reducing gold (III) chloride trihydrate using branched polyethyleneimine (bPEI). These nanoparticles increase gel stiffness from ≈91 to ≈146 kPa, enhance electrical conductivity of collagen hydrogels from ≈40 to 49–68 mS cm−1, and allow slow and steady release of loaded drugs. Engineered cardiac tissues based on bPEI-AuNP-collagen hydrogels and either primary or human induced pluripotent stem cell (hiPSC)-derived cardiomyocytes show enhanced beating properties. hiPSC-derived cardiomyocytes exhibit more aligned and wider sarcomeres in bPEI-AuNP-collagen hydrogels compared to collagen hydrogels. Furthermore, the presence of bPEI-AuNPs result in advanced electrical coupling evidenced by synchronous and homogenous calcium flux throughout the tissue. RNA-seq analyses are in agreement with these observations. Collectively, this data demonstrate the potential of bPEI-AuNP-collagen hydrogels to improve tissue engineering approaches to prevent heart failure and possibly treat diseases of other electrically sensitive tissues.
CRIS-Team Scopus Importer:2023-04-21
Keywords: collagen; gold nanoparticles; heart; tissue engineering

DEVELOPMENT OF APPROACHES FOR A TWO-LAYER PATCH COMBINING ELECTROSPINNING AND 3D PRINTING WITH IMPROVED ELECTRICAL STIMULUS TRANSMISSION AND SELF-REGULATING VISCOELASTIC PROPERTIES FOR APPLICATION IN CARDIAC TISSUE ENGINEERING - Boccaccini, Aldo R.; Vogt, Lena; Ruther, Florian; Roshanbinfar, Kaveh; Engel, Felix (TISSUE ENGINEERING PART A, 2022)
CRIS-Team WoS Importer:2022-08-12

Electrically Conductive Collagen-PEDOT:PSS Hydrogel Prevents Post-Infarct Cardiac Arrhythmia and Supports hiPSC-Cardiomyocyte Function - Roshanbinfar, Kaveh; Schiffer, Miriam; Carls, Esther; Angeloni, Miriam; Kolesnik-Gray, Maria; Schrüfer, Stefan; Schubert, Dirk W.; Ferrazzi, Fulvia; Krstic, Vojislav; Fleischmann, Bernd K.; Roell, Wilhelm; Engel, Felix (Advanced Materials, 2024)
Myocardial infarction (MI) causes cell death, disrupts electrical activity, triggers arrhythmia, and results in heart failure, whereby 50–60% of MI-associated deaths manifest as sudden cardiac deaths (SCD). The most effective therapy for SCD prevention is implantable cardioverter defibrillators (ICDs). However, ICDs contribute to adverse remodeling and disease progression and do not prevent arrhythmia. This work develops an injectable collagen-PEDOT:PSS (poly(3,4-ethylenedioxythiophene) polystyrene sulfonate) hydrogel that protects infarcted hearts against ventricular tachycardia (VT) and can be combined with human induced pluripotent stem cell (hiPSC)-cardiomyocytes to promote partial cardiac remuscularization. PEDOT:PSS improves collagen gel formation, micromorphology, and conductivity. hiPSC-cardiomyocytes in collagen-PEDOT:PSS hydrogels exhibit near-adult sarcomeric length, improved contractility, enhanced calcium handling, and conduction velocity. RNA-sequencing data indicate enhanced maturation and improved cell-matrix interactions. Injecting collagen-PEDOT:PSS hydrogels in infarcted mouse hearts decreases VT to the levels of healthy hearts. Collectively, collagen-PEDOT:PSS hydrogels offer a versatile platform for treating cardiac injuries.
CRIS-Team Scopus Importer:2024-05-10
Keywords: arrhythmia; cardiac tissue engineering; collagen; electrically conductive; PEDOT:PSS

Electroconductive Biohybrid Hydrogel for Enhanced Maturation and Beating Properties of Engineered Cardiac Tissues - Roshanbinfar, Kaveh; Vogt, Lena; Greber, Boris; Diecke, Sebastian; Boccaccini, Aldo R.; Scheibel, Thomas; Engel, Felix (Advanced Functional Materials, 2018)
Keywords: electroconductive hydrogels; maturation; tissue engineering; heart; hiPSC

Enhancement of engineered cardiac tissues by promotion of hiPSC-cardiomyocyte proliferation - Hesselbarth, Ramona; Esser, Tilman; Roshanbinfar, Kaveh; Schrüfer, Stefan; Schubert, Dirk W.; Engel, Felix (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Enhancing biofabrication: Shrink-resistant collagen-hyaluronan composite hydrogel for tissue engineering and 3D bioprinting applications - Roshanbinfar, Kaveh; Evans, Austin Donnelly; Samanta, Sumanta; Kolesnik-Gray, Maria; Fiedler, Maren; Krstic, Vojislav; Engel, Felix; Oommen, Oommen P. (Biomaterials, 2025)
Biofabrication represents a promising technique for creating tissues for regeneration or as models for drug testing. Collagen-based hydrogels are widely used as suitable matrix owing to their biocompatibility and tunable mechanical properties. However, one major challenge is that the encapsulated cells interact with the collagen matrix causing construct shrinkage. Here, we present a hydrogel with high shape fidelity, mimicking the major components of the extracellular matrix. We engineered a composite hydrogel comprising gallic acid (GA)-functionalized hyaluronic acid (HA), collagen I, and HA-coated multiwall carbon nanotubes (MWCNT). This hydrogel supports cell encapsulation, exhibits shear-thinning properties enhancing injectability and printability, and importantly significantly mitigates shrinkage when loaded with human fibroblasts compared to collagen I hydrogels (∼20 % vs. > 90 %). 3D-bioprinted rings utilizing human fibroblast-loaded inks maintain their shape over 7 days in culture. Furthermore, inclusion of HAGA into collagen I hydrogels increases mechanical stiffness, radical scavenging capability, and tissue adhesiveness. Notably, the here developed hydrogel is also suitable for human induced pluripotent stem cell-derived cardiomyocytes and allows printing of functional heart ventricles responsive to pharmacological treatment. Cardiomyocytes behave similar in the newly developed hydrogels compared to collagen I, based on survival, sarcomere appearance, and calcium handling. Collectively, we developed a novel material to overcome the challenge of post-fabrication matrix shrinkage conferring high shape fidelity.
CRIS-Team Scopus Importer:2025-02-21
Keywords: 3D bioprinting; Cardiac; Hydrogel; Shrink-resistant; Shrinkage; Tissue engineering

Enhancing Form Stability: Shrink-Resistant Hydrogels Made of Interpenetrating Networks of Recombinant Spider Silk and Collagen-I - Ng, Xuen J.; Esser, Tilman; Trossmann, Vanessa T.; Rudisch, Christoph; Fiedler, Maren; Roshanbinfar, Kaveh; Lamberger, Zan; Stahlhut, Philipp; Lang, Gregor; Scheibel, Thomas; Engel, Felix (Advanced Healthcare Materials, 2025)
Tissue engineering enables the production of tissues and organ-like structures as models for drug testing and mechanistical studies or functional replacements for injured tissues. Available cytocompatible materials are limited in number, suffer from insufficient mechanical properties, and cells interacting with them often cause construct shrinkage. As shape is important for function, identifying cytocompatible, shrink-resistant materials are a major aim. Here, it is shown that hydrogels made of interpenetrating networks of collagen-I and recombinant spider silk protein eADF4(C16)-RGD nanofibrils exhibit synergistic and tunable mechanical properties. Composite hydrogels allow cell adhesion and spreading and are resistant to shrinkage mediated by fibroblasts, C2C12 myoblasts, and human induced pluripotent stem cell (hiPSC)-derived cardiomyocytes. Myoblasts differentiate and fuse into myotubes, and hiPSC-cardiomyocytes can be cultured long-term, show spontaneous contractions, and remain drug responsive. Collectively, a novel composite material is developed to overcome the challenge of post-fabrication matrix shrinkage conferring high shape fidelity suitable for tissue engineering.
CRIS-Team Scopus Importer:2025-04-11
Keywords: biopolymer; cardiac tissue engineering; compaction; heart; shrinkage

Incorporation of montmorillonite into microfluidics-generated chitosan microfibers enhances neuron-like PC12 cells for application in neural tissue engineering - Katoli, Zahra; Navaei-Nigjeh, Mona; Mirzababaei, Soheyl; Sabahi, Hossein; Baeeri, Maryam; Akrami, Mohammad; Roshanbinfar, Kaveh; Engel, Felix; Abdollahi, Mohammad (Carbohydrate Polymers, 2024)
The complexity in structure and function of the nervous system, as well as its slow rate of regeneration, makes it more difficult to treat it compared to other tissues. Neural tissue engineering aims to create an appropriate environment for nerve cell proliferation and differentiation. Fibrous scaffolds with suitable morphology and topography and better mimicry of the extracellular matrix have been promising for the alignment and migration of neural cells. On this premise, to improve the properties of the scaffold, we combined montmorillonite (MMT) with chitosan (CS) polymer and created microfibers with variable diameters and varied concentrations of MMT using microfluidic technology and tested its suitability for the rat pheochromocytoma cell line (PC12). According to the findings, CS/MMT 0.1 % compared to CS/MMT 0 % microfibers showed a 201 MPa increase in Young's modulus, a 68 mS/m increase in conductivity, and a 1.4-fold increase in output voltage. Analysis of cell mitochondrial activity verified the non-toxicity, resulting in good cell morphology with orientation along the microfiber. Overall, the results of this project showed that with a low concentration of MMT, the properties of microfibers can be significantly improved and a suitable scaffold can be designed for neural tissue engineering.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Chitosan; Microfiber; Microfluidic technology; Montmorillonite; Neural tissue engineering

Influence of AAV vector tropism on long-term expression and Fc-γ receptor binding of an antibody targeting SARS-CoV-2 - Wagner, Jannik; Müller-Schmucker, Sandra; Wang, Wenjun; Arnold, Philipp; Uhlig, Nadja; Issmail, Leila; Eberlein, Valentina; Damm, Dominik; Roshanbinfar, Kaveh; Enßer, Armin; Oltmanns, Friederike; Peter, Antonia Sophia; et al. (Communications Biology, 2024)
Long-acting passive immunization strategies are needed to protect immunosuppressed vulnerable groups from infectious diseases. To further explore this concept for COVID-19, we constructed Adeno-associated viral (AAV) vectors encoding the human variable regions of the SARS-CoV-2 neutralizing antibody, TRES6, fused to murine constant regions. An optimized vector construct was packaged in hepatotropic (AAV8) or myotropic (AAVMYO) AAV capsids and injected intravenously into syngeneic TRIANNI-mice. The highest TRES6 serum concentrations (511 µg/ml) were detected 24 weeks after injection of the myotropic vector particles and mean TRES6 serum concentrations remained above 100 µg/ml for at least one year. Anti-drug antibodies or TRES6-specific T cells were not detectable. After injection of the AAV8 particles, vector mRNA was detected in the liver, while the AAVMYO particles led to high vector mRNA levels in the heart and skeletal muscle. The analysis of the Fc-glycosylation pattern of the TRES6 serum antibodies revealed critical differences between the capsids that coincided with different binding activities to murine Fc-γ-receptors. Concomitantly, the vector-based immune prophylaxis led to protection against SARS-CoV-2 infection in K18-hACE2 mice. High and long-lasting expression levels, absence of anti-drug antibodies and favourable Fc-γ-receptor binding activities warrant further exploration of myotropic AAV vector-based delivery of antibodies and other biologicals.
CRIS-Team Scopus Importer:2024-07-26

Microfluidically fabricated fibers containing pancreatic islets and mesenchymal stromal cells improve longevity and sustained normoglycemia in diabetic rats - Navaei-Nigjeh, Mona; Mirzababaei, Soheyl; Ghiass, Mohammad Adel; Roshanbinfar, Kaveh; Gholami, Mahdi; Abdollahi, Mohammad (Biofabrication, 2022)
Type 1 diabetes mellitus is an autoimmune disease characterized by the loss of pancreatic isletβcells. Insulin injections and pancreas transplants are currently available therapies. The former requires daily insulin injections, while the latter is constrained by donor organ availability. Islet transplantation is a promising alternative treatment for type 1 diabetes mellitus that may overcome the limitations of previous techniques. Two challenges, however, must be addressed: limited cell retention as a result of the immune response and limited function of the transplanted cells that survive. To address these problems, we developed a microfluidic technology for a one-step generation of islet-laden fibers to protect them from the immune response. This approach enables continuous generation of microfibers with a diameter suitable for islet encapsulation (275µm). We, then, transplanted islet-laden fibers into diabetic Wistar rats. While islet-laden fibers alone were unable to restore normoglycemia in diabetic rats, adding mesenchymal stromal cells (MSCs) restored normoglycemia for an extended time. It increased the animals' lifespan by up to 75 d. Additionally, it improved the glucose-stimulated response of islets to the point where there was no significant difference between the treatment group and the healthy animals. Additionally, the presence of MSCs suppressed the immune response, as seen by decreased levels of pro-inflammatory cytokines such as tumor necrosis factor-α. Taken together, these fibers including islet and MSCs provide a versatile platform for concurrently improving cell preservation and functioning followingin vivotransplantation.
CRIS-Team Scopus Importer:2022-12-16
Keywords: cell encapsulation; cell-laden fiber; diabetes; mesenchymal stromal cells; microfiber; microfluidics; pancreatic islet transplantation

Nanofibrous Composite with Tailorable Electrical and Mechanical Properties for Cardiac Tissue Engineering - Roshanbinfar, Kaveh; Vogt, Lena; Ruther, Florian; Roether, Judith; Boccaccini, Aldo R.; Engel, Felix (Advanced Functional Materials, 2019)
Cardiac tissue engineering is a promising strategy to prevent functional deterioration or even to enhance cardiac function upon myocardial infarction. Here, electrospun fiber mats containing different combinations of electrically conductive polyaniline, collagen, and/or hyaluronic acid are assessed regarding material properties and compatibility with cardiomyocyte attachment and function. Microstructure analysis reveals that collagen fiber mats contain a wide range of fiber diameters after crosslinking (from ≈300 nm to ≈5 µm); all other fiber mats contain fibers in the range of ≈120 to ≈300 nm. Fiber mats exhibit comparable electrical conductivity to and greater mechanical properties than the native human myocardium, which is considered beneficial. Cell–matrix interaction analysis utilizing postnatal rat cardiomyocytes reveals that the fiber mats are non-cytotoxic and permit cell attachment and contraction. Fiber mats containing collagen (9.89%), hyaluronic acid (1.1%), and polyaniline (PANi, 1.34%) exhibit the most favorable properties with longer contraction time, higher contractile amplitude, and lower beating rates. Improved contraction is accompanied by increased connexin 43 expression. Importantly, this fiber mat is a suitable material for human-induced pluripotent stem cell–derived cardiomyocytes regarding cytotoxicity, cell attachment, and function. Collectively, these data demonstrate that fiber mats made of collagen, hyaluronic acid, and polyaniline are promising materials for cardiac tissue engineering.
CRIS-Team Scopus Importer:2019-12-31
Keywords: collagen; electroconductive; electrospinning; heart; hyaluronic acid; polyaniline; tissue engineering

Nephronectin Is Required for Vascularization in Zebrafish and Sufficient to Promote Mammalian Vessel-Like Structures in Hydrogels for Tissue Engineering. - Patra, Chinmoy; Rayrikar, Amey; Wagh, Ganesh; Kleefeldt, Florian; Roshanbinfar, Kaveh; Cop, Florian; Nikolic, Iva; Schmidt, Mirko H.H.; Acker-Palmer, Amparo; Ergün, Süleyman; Engel, Felix (Journal of the American Heart Association, 2025)
BACKGROUND: Organs and tissues need to be vascularized during development. Similarly, vascularization is required to engineer thick tissues. How vessels are formed during organogenesis is not fully understood, and vascularization of engineered tissues remains a significant challenge. METHODS AND RESULTS: Here, we show that the extracellular matrix protein nephronectin is required for vascularization during zebrafish development as well as adult fin regeneration and is sufficient to promote mammalian vessel formation and maturation. Nephronectin a morphants and mutants exhibit diminished axial vein sprouting and posterior intersegmental vessel growth. Notably, the angiogenesis-associated integrins itgav and itgb3.1 are coexpressed with nephronectin a in the region of the caudal vein plexus and posterior somites; nephronectin binds to integrin alpha-V/integrin beta-3.1 (ITGAV/ITGB3.1), and itgav morphants phenocopy nephronectin a mutants. In addition, nephronectin a mutants showed decreased vessel maturation compared with wild-type siblings during caudal fin regeneration in adult zebrafish. Moreover, nephronectin promotes mammalian endothelial cell migration and tube formation in 2D and 3-dimensional in vitro tissue culture. Further, nephronectin enhances vascular endothelial growth factor-induced periaortic vascular capillary interconnectivity, vessel diameter, and vessel stability. CONCLUSIONS: Collectively, our results identify nephronectin as a proangiogenic factor during embryonic development, which can be used to improve the vascularization of engineered tissues.
EVALuna2:583978

Potential of graphene-based nanomaterials for cardiac tissue engineering - Edrisi, Fatemeh; Baheiraei, Nafiseh; Razavi, Mehdi; Roshanbinfar, Kaveh; Imani, Rana; Jalilinejad, Negin (Journal of Materials Chemistry B, 2023)
Cardiovascular diseases are the primary cause of death worldwide. Despite significant advances in pharmacological treatments and surgical interventions to restore heart function after myocardial infarction, it can progress to heart failure due to the restricted inherent potential of adult cardiomyocytes to self-regenerate. Hence, the evolution of new therapeutic methods is critical. Nowadays, novel approaches in tissue engineering have assisted in restoring biological and physical specifications of the injured myocardium and, hence, cardiac function. The incorporation of a supporting matrix that could mechanically and electronically support the heart tissue and stimulate the cells to proliferate and regenerate will be advantageous. Electroconductive nanomaterials can facilitate intracellular communication and aid synchronous contraction via electroactive substrate creation, preventing the issue of arrhythmia in the heart. Among a wide range of electroconductive materials, graphene-based nanomaterials (GBNs) are promising for cardiac tissue engineering (CTE) due to their outstanding features including high mechanical strength, angiogenesis, antibacterial and antioxidant properties, low cost, and scalable fabrication. In the present review, we discuss the effect of applying GBNs on angiogenesis, proliferation, and differentiation of implanted stem cells, their antibacterial and antioxidant properties, and their role in improving the electrical and mechanical properties of the scaffolds for CTE. Also, we summarize the recent research that has applied GBNs in CTE. Finally, we present a concise discussion on the challenges and prospects.
CRIS-Team Scopus Importer:2023-08-18

Promoting vascularization for tissue engineering constructs: current strategies focusing on HIF-regulating scaffolds - Esser, Tilman; Roshanbinfar, Kaveh; Engel, Felix (Expert Opinion on Biological Therapy, 2018)
INTRODUCTION: Vascularization remains one of the greatest yet unmet challenges in tissue engineering. When engineered tissues are scaled up to therapeutically relevant dimensions, their demand of oxygen and nutrients can no longer be met by diffusion. Thus, there is a need for perfusable vascular structures. Hypoxia-inducible factors (HIF) act as transcriptional oxygen sensors and regulate a multitude of genes involved in adaptive processes to hypoxia, including angiogenesis. Thus, targeting HIFs is a promising strategy to induce vascularization of engineered tissues. Areas covered: Here we review current vascularization strategies and summarize the present knowledge regarding activation of HIF signaling by ions, iron chelating agents, α-Ketoglutarate (αKG) analogues, and the lipid-lowering drug simvastatin to induce angiogenesis. Specifically, we focus on the incorporation of HIF-activating agents into biomaterials and scaffolds for controlled release. Expert opinion: Vascularization of tissue constructs through activation of upstream regulators of angiogenesis offers advantages but also suffers from drawbacks. HIFs can induce a complete angiogenic program; however, this program appears to be too slow to vascularize larger constructs before cell death occurs. It is therefore crucial that HIF-activation is combined with cell protective strategies and prevascularization techniques to obtain fully vascularized, vital tissues of therapeutically relevant dimensions.
EVALuna2:102206

Recombinant spider silk protein eADF4(C16)-RGD coatings are suitable for cardiac tissue engineering - Kramer, Johannes P.M.; Aigner, Tamara B.; Petzold, Jana; Roshanbinfar, Kaveh; Scheibel, Thomas; Engel, Felix (Scientific Reports, 2020)
Cardiac tissue engineering is a promising approach to treat cardiovascular diseases, which are a major socio-economic burden worldwide. An optimal material for cardiac tissue engineering, allowing cardiomyocyte attachment and exhibiting proper immunocompatibility, biocompatibility and mechanical characteristics, has not yet emerged. An additional challenge is to develop a fabrication method that enables the generation of proper hierarchical structures and constructs with a high density of cardiomyocytes for optimal contractility. Thus, there is a focus on identifying suitable materials for cardiac tissue engineering. Here, we investigated the interaction of neonatal rat heart cells with engineered spider silk protein (eADF4(C16)) tagged with the tripeptide arginyl-glycyl-aspartic acid cell adhesion motif RGD, which can be used as coating, but can also be 3D printed. Cardiomyocytes, fibroblasts, and endothelial cells attached well to eADF4(C16)-RGD coatings, which did not induce hypertrophy in cardiomyocytes, but allowed response to hypertrophic as well as proliferative stimuli. Furthermore, Kymograph and MUSCLEMOTION analyses showed proper cardiomyocyte beating characteristics on spider silk coatings, and cardiomyocytes formed compact cell aggregates, exhibiting markedly higher speed of contraction than cardiomyocyte mono-layers on fibronectin. The results suggest that eADF4(C16)-RGD is a promising material for cardiac tissue engineering.
CRIS-Team Scopus Importer:2020-06-09

Static magnetic field enhances the bone remodelling capacity of human demineralized bone matrix in a rat animal model of cranial bone defects - Hosseini, Seyed Jamal; Parsaei, Houman; Moosavifar, Mir Javad; Tavakoli, Narjes; Ahadi, Reza; Roshanbinfar, Kaveh (Journal of Materials Chemistry B, 2024)
The regeneration of bone defects that exceed 2 cm is a challenge for the human body, necessitating interventional therapies. Demineralized bone matrices (DBM) derived from biological tissues have been employed for bone regeneration and possess notable osteoinductive and osteoconductive characteristics. Nevertheless, their efficiency in regenerating critically sized injuries is limited, and therefore additional signaling cues are required. Thanks to the piezoelectric properties of the bone, external physical stimulation is shown to accelerate tissue healing. We have implanted human DBM in critically sized cranial bone defects in rat animal models and exposed them to an external magnetic field (1 T) to enhance endogenous bone formation. Our in vitro experiments showed the superior cytocompatibility of DBM compared to cell culture plates. Furthermore, alkaline phosphatase activity after 14 days and Alizarin red staining at 28 days demonstrated differentiation of rat bone marrow mesenchymal stem cells into bone lineage on DBM. Computer tomography images together with histological analyses showed that implanting DBM in the injured rats significantly enhanced bone regeneration. Notably, combining DBM transplantation with a 2 h daily exposure to a 1 T magnetic field for 2 weeks (day 7 to 21 post-surgery) significantly improved bone regeneration compared to DBM transplantation alone. This research indicates that utilizing external magnetic stimulation significantly enhances the potential of bone allografts to regenerate critically sized bone defects.
CRIS-Team Scopus Importer:2024-04-26

Stem Cells and Their Cardiac Derivatives for Cardiac Tissue Engineering and Regenerative Medicine - Roshanbinfar, Kaveh; Esser, Tilman; Engel, Felix (Antioxidants & Redox Signaling, 2020)
Significance: Heart failure is among the leading causes of morbidity worldwide with a 5-year mortality rate of similar to 50%. Therefore, major efforts are invested to reduce heart damage upon injury or maintain and at best restore heart function.
CRIS-Team WoS Importer:2020-12-04